Penerapan Terapi Senam Otak Dalam Meningkatkan Kesehatan Kognitif Lansia - Putri, Rona Sari Mahaji; Devi, Hilda Mazarina (Poltekkes Kemenkes Kendari, 2024)
As older people get older, there is a decline in the elderly's memory. Many elderly people forget something. If left unchecked, memory loss will ultimately impact the quality of life of the elderly. Memory as part of the cognitive function of the elderly needs to be improved. The aim of this community service is to provide brain exercise therapy in an effort to improve cognitive function in the elderly, as a preventive and promotive activity for the health of the elderly. Brain exercise therapy was attended by 12 elderly people in the RT 06 RW 01 area, Tanjungrejo sub-district, Sukun District, Malang City, which was carried out at the house of one of the residents at 07.30-11.00 WIB. The activity is carried out in 2 sessions, namely a training session and a therapy session, consisting of 9 hand movements that train the balance of the right and left brain. Community service activities have been carried out and are going well, the elderly expressed their enthusiasm for this activity, which was conveyed through sentences and body gestures as well as excitement in doing brain exercise movements. With this activity, the Community Service concluded that this activity is not only useful for improving the cognitive function of the elderly if done regularly, but also reduces the mental and mental burden of the elderly through free laughter while doing exercise.